2015
DOI: 10.1128/jb.02579-14
|View full text |Cite
|
Sign up to set email alerts
|

Another Look at Mutations in Ribosomal Protein S4 Lends Strong Support to the Domain Closure Model

Abstract: Ribosomes employ a "kinetic discrimination" mechanism, in which correct substrates are incorporated more rapidly than incorrect ones. The structural basis of this mechanism may involve 30S domain closure, a global conformational change that coincides with codon recognition. In a direct screen for fidelity-altering mutations, Agarwal Ribosomes synthesize proteins on the basis of mRNA templates by using a diverse pool of aminoacyl-tRNA (aa-tRNA) substrates. In each round of elongation, EF-Tu catalyzes the bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…A recent reevaluation of S4/S5 mutations showed that all C-terminal truncations of S4 confer a ram phenotype (Agarwal et al 2015). These truncations undoubtedly destabilize the open conformation of the subunit, lending strong support to the idea that domain closure contributes to GTPase activation (Ogle and Ramakrishnan 2005;Voorhees et al 2010;Fredrick 2015). Ram mutations in h8/h14 act by disrupting bridge B8.…”
Section: +mentioning
confidence: 95%
See 1 more Smart Citation
“…A recent reevaluation of S4/S5 mutations showed that all C-terminal truncations of S4 confer a ram phenotype (Agarwal et al 2015). These truncations undoubtedly destabilize the open conformation of the subunit, lending strong support to the idea that domain closure contributes to GTPase activation (Ogle and Ramakrishnan 2005;Voorhees et al 2010;Fredrick 2015). Ram mutations in h8/h14 act by disrupting bridge B8.…”
Section: +mentioning
confidence: 95%
“…Genetic and structural evidence suggest that formation of the closed (on) state involves not only rearrangement of the A site but also conformational changes elsewhere, such as disruption of bridge B8 and inward rotation of the 30S shoulder (Ogle and Ramakrishnan 2005;McClory et al 2010;Fagan et al 2013;Fredrick 2015). Binding of tRNA to the 30S A site promotes the open-to-closed transition, and vice versa, as depicted in the thermodynamic cycles of Figure 4.…”
Section: Conformational Dynamics Of the 30s Subunit That Impact Decodingmentioning
confidence: 99%
“…By establishing that the ΔV200 and E201* uS4 alterations in both E.coli and S. enterica have a ram phenotype, the results presented here help resolve a puzzling inconsistency in the literature [8]. With the exception of ΔV200 and E201 and Q53L in S. enterica all other uS4 mutants isolated as suppressors of the streptomycin dependence, or the slower growth phenotypes associated with uS12-alterations have proved to be error-prone.…”
Section: Resultsmentioning
confidence: 58%
“…However, at least some interface-disrupting uS4 mutants have an error-restrictive phenotype, which is difficult to reconcile with the open-closed model [8]. These uS4 mutations, isolated in Salmonella enterica carry a deletion of Val200 (ΔV200) or a truncation at Glu201 (E201*) [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, codon-anticodon pairing in the 30S A site induces movement of the 30S head and shoulder domain towards each other around the A site, resulting in a “closed” conformation 9 , which is thought to activate elongation factor EF-Tu during the decoding process 10; 11; 12; 13 . Moreover, two major large-scale rearrangements, rotation of 30S head domain relative to the rest of the subunit, as well as the rotation between 30S and 50S subunits, have been attributed to various steps of translation, including subunit joining 14 , translocation 15; 16; 17; 18; 19; 20; 21 , peptide release 22; 23 , and ribosome recycling 24 .…”
mentioning
confidence: 99%